Sexual Violence against Wife Based on Law No. 23 of 2004 Concerning Elimination of Violence in Households and Islamic Law (Analysis of the Decisions of the Bangil, Denpasar and Medan District Courts) - Masdoki (Britain International for Academic Research (BIAR) Publisher, 2021)
This study aims to determine what forms of sexual violence against wives are based on Law no. 23 of 2004 and Islamic Law. To find out what forms of sexual violence against wives in the decision of the Bangil District Court No. 912/Pid/B/2011/PN.Bgl, Denpasar District Court Decision No.89/Pid.Sus/2014/PN.Dps and Medan District Court Decision No.264/Pid.Sus/2018/PN Mdn. To find out what were the basis for the judge's consideration in giving a decision at the Bangil District Court, the Denpasar District Court decision, and the Medan District Court decision regarding sexual violence against wives. Qualitative research was conducted with a revelatory approach, a statute approach, a case approach and a comparative approach. The results of this study indicate that: (1) forms of sexual violence against wives based on Law no. 23 of 2004 and Islamic Law is any act in the form of coercion of sexual relations, in an inappropriate and/or inappropriate manner, forcing sexual relations with other people for commercial purposes and/or for specific purposes. (2) the forms of sexual violence against wives in the decisions of the Bangil District Court, Denpasar District Court decisions and Medan. (3) The consideration of the Bangil District Court judge.